Effect of improving aerobics classes at the level of flexibility of female students - Pogrebniak I. M.; Kudelko V. E.; Nagovitsina O. P. (Kharkov National Pedagogical University, 2013)
The features of the influence of a set of special exercises with gymnastic stick and elements of stretching to develop flexibility while improving aerobics classes. In pedagogical experiment involved 20 girls 17 - 18 years old, first-year student. During the final part of the session used a set of special exercises aimed at increasing the range of motion when the torso and the mobility of the shoulder joints. The dynamics of indicators of flexibility. Determined that the selected set of special exercises in the classroom improving aerobics has a positive effect on the performance increase flexibility. Significant increase in the results can be seen in test 1 tilt body forward, which is characterized by increased mobility of the joints of the spine. It was determined that the transfer of gymnastic stick behind his back indicates an increase in the mobility of the shoulder joints.